2015
DOI: 10.1136/bcr-2015-210726
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone in the elderly: risk of extrapyramidal acute events

Abstract: Trazodone is a second-generation atypical antidepressant exercising selective inhibitory action on the transport of serotonin. It also has an antagonist effect, similar to nefazodone, on the 5HT1 and 5HT2 receptors, probably due to the therapeutic effects of such substances. It is very effective in the treatment of depression, in anxiety and insomnia. Its known side effects mainly occur with prolonged use of daily doses of 150–200 mg. The ability to enhance drowsiness may be associated with some risk in elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A recent review highlighted the dearth of comparative data for older adults and suggested that low-dose trazodone should be recommended for insomnia only if the individual has comorbid depression. 23 Consensus panels on dementia treatment have also concluded that there is not clear evidence for, or against, a recommendation for use of lowdose trazodone in BPSD, 24 and low-dose trazodone use has been linked to falls 25,26 , nausea and vomiting, 23,27 and extrapyramidal symptoms 28 .…”
mentioning
confidence: 99%
“…A recent review highlighted the dearth of comparative data for older adults and suggested that low-dose trazodone should be recommended for insomnia only if the individual has comorbid depression. 23 Consensus panels on dementia treatment have also concluded that there is not clear evidence for, or against, a recommendation for use of lowdose trazodone in BPSD, 24 and low-dose trazodone use has been linked to falls 25,26 , nausea and vomiting, 23,27 and extrapyramidal symptoms 28 .…”
mentioning
confidence: 99%
“…To the authors' knowledge, there are five reports of parkinsonism secondary to trazodone in the literature. 2,[4][5][6][7] Herein, we present a case of a male who developed parkinsonism after a short-duration intake of a moderate dose of trazodone.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs associated with causation of EPS include the following: SSRIs like fluoxetine, paroxetine, sertraline, amisulpiride, typical antipsychotics like haloperidol, chlorpromazine, flupenthixol, fluphenazine pimozide, prochlorperazine, atypicals like clozapine, quetiapine, risperidone, sulpiride, thioridazine, trifluperazine, zuclopenthixol, and zotepine. Some other drugs that are responsible for drug-induced Parkinson's disease also include amiodarone, cinnarazine, lithium, methyldopa, metoclopramide, and trazodone [11,12] .…”
Section: Role Of Other Drugs In Causing Epsmentioning
confidence: 99%